Pengaruh Handbook Overweight Terhadap Penurunan Asupan Karbohidrat di SMP Frater Kendari - Abadi, Ellyani; Sunarsih, Sunarsih; Usman, Andi Nilawati (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2018)
The prevalence of overweight in adolescents in the Brother Middle School is 14.1% (exceeding the standard for nutritional problems of 10%), therefore innovation is needed in the form of giving a handbook to overcome the problem of overweight. This study aims to determine the effect of overweight handbook on adolescent weight loss at Brother Kendari Junior High School. This research is a quantitative research (pre-experimental) with a pre-test-post-test design. This research was conducted on May 7 - July 14 2018. The population was all overweight Brothers Private Junior High School students, namely 38 people, a sample of 32 people was obtained by simple random sampling. Carbohydrate intake data collection form 3 x 24 hour recall. The data was measured 4 times and analyzed using the paired T-test. The results showed that the average (mean) intake of KH for adolescents increased, namely before being given the overweight handbook it was 327.0 g, then after being given the overweight handbook, the intake of KH for adolescents was 268.6 g. The average increase in KH intake was 58, 4 gr. The results of the paired T-test on carbohydrate intake obtained p value (0.000) <α (0.05). The conclusion of this study is that there is an effect of overweight handbook on decreasing carbohydrate intake of overweight adolescents at Brothers Kendari Junior High School. It is recommended for the Brother Junior High School overweight students to always read the overweight handbook and limit foods high in carbohydrates and for the Brother Junior High School students to regularly provide education about limiting carbohydrate intake to overweight sufferers by using a handbook.